Pemilihan Umum Serentak yang Berintegritas sebagai Pembaruan Demokrasi Indonesia - Achmad Edi Subiyanto (The Constitutional Court of the Republic of Indonesia, 2020)
The implementation of the General Election of the President and Vice President after the General Election of Members of the House of Representatives, the Regional Representatives Council, and the Regional People’s Legislative Assembly turned out to be unable to become a tool for transforming social change in the desired direction. The experience of these constitutional practices did not strengthen the governance system desired by the 1945 Constitution of the Republic of Indonesia. That, through the Decision of the Constitutional Court General Elections are held simultaneously. However, there are weaknesses in the preparation of the policy for implementing general elections simultaneously. The decision of the Constitutional Court should be followed by an evidence-based policy making process with strong data and based on simulations of implementation. Therefore, the burden of organizing General Elections can be identified from the start and steps to minimize risk can be considered if things happen that are not desirable. Then what is equally important is that it needs to be evaluated on the issue of the integrity of the organizers or participants of the General Election, for example by tightening the recruitment system, so that it can create simultaneous elections with integrity in the future